Biological Degradation Of Empty Fruit Bunch With Biosurfactants And Palm Oil Mill Effluent Sludge By Composting - Azhan, Wan Nur Arisya Najwa Wan Zainal (Universiti Sains Malaysia, 2021)
Composting is a modern waste treatment method used to treat the empty fruit bunch (EFB), one of the primary feedstock of solid palm oil. About 20% EFB is produced in crude palm oil production for every ton of fresh fruit bunch. EFB composting produces EFB compost that can benefit agriculture. This study aimed to look into the quality of EFB compost produced by composting EFB with biosurfactants. The composting procedure was carried out in a laboratory setting using 500 ml Erlenmeyer flasks at 30oC and 50oC. The composting sample consists of EFB, EFB with POME and EFB with POME and biosurfactants. The mixture of EFB: POME: Biosurfactants was prepared in the ratio of 10:1:1.5, respectively. Several parameters need to be examined, such as pH, electrical conductivity, volatile solids, moisture content, C/N ratio, phosphorus, and enzymes activity. To evaluate the effect of consistent temperatures on the properties of EFB compost, temperatures were kept constant throughout the process for 35 days. At 30oC, the EFB compost created from composting EFB with palm oil mill effluent and biosurfactants performed better. The carbon to nitrogen ratio of the EFB compost was 5.5, the phosphorus content was 2.19%, the moisture content was 82.02%, and the pH was 8.16. The presence of biosurfactants in the composting process can produce adequate compost and reduce the consuming time to stabilize the EFB product during composting.